Challenges in Implementing Competency-based English Language Teaching at University Level - Angelika Riyandari (TEFLIN, 2004)
Competency-based curriculum has been widely implemented by many higher institutions in Indonesia. It is expected that the competency-based curriculum, which puts more emphasis on the needs of job market, prepare students for specified tasks. Competency in a general sense can be seen from the task performance. English language competency is one of the basic competencies which should be acquired by a university graduate in order to enter international market and survive the global competition. The institution which offers English language as part of their curriculum must answer the demand for an English language competent graduate by preparing the best way to teach the language. This article examines the steps to develop a competency-based English language teaching where students attitude and achievement comprise the important segments of evaluation. It focuses on the challenges, which will probably be faced by the teachers in implementing this competency-based teaching at the university level.